Titanium dioxide nanotubes added to glass ionomer cements affect S. mutans viability and mechanisms of virulence - ARAÚJO,Isaac Jordão de Souza (2021)
Abstract This in vitro study evaluated the impact of TiO2 nanotubes (n-TiO2) incorporated into glass ionomer cement (GIC) on Streptococcus mutans (S. mutans) characteristics at cellular and molecular levels. n-TiO2, synthesized by the alkaline method (20 nm in size), was added to Ketac Molar EasyMix® at 0%, 3%, 5%, and 7% by weight. S. mutans strains were cultured on GIC disks with addition or not of n-TiO2 for 1, 3, and 7 days and the following parameters were assessed: inhibition halo (mm) (n=3/group); cell viability (live/dead) (n=5/group); cell morphology (SEM) (n=3/group); and gene expression by real-time PCR (vicR, covR, gtfB, gtfC, and gtfD) (n=6/group). The data were analyzed by the Kruskal-Wallis test, repeated-measures ANOVA or two-way ANOVA, and Tukey’s and Dunn’s post-hoc tests (α=0.05). The agar diffusion test showed a higher antibacterial property for 5% n-TiO2 compared with 3% and 7% (p<0.05) with no effect of time (1, 3, and 7 days). The cell number was significantly affected by all n-TiO2 groups, while viability was mostly affected by 3% and 5% n-TiO2, which also affected cell morphology and organization. Real-time PCR demonstrated that n-TiO2 reduced the expression of covR when compared with GIC with no n-TiO2 (p<0.05), with no effect of time, except for 3% n-TiO2 on vicR expression. Within-group and between-group analyses revealed n-TiO2 did not affect mRNA levels of gtfB, gtfC, and gtfD (p>0.05). Incorporation of n-TiO2 at 3% and 5% potentially affected S. mutans viability and the expression of key genes for bacterial survival and growth, improving the anticariogenic properties of GIC.